On-Job Training in Rangeland Restoration - Ouled Belgacem, Azaiez; Hassan, Sawsan; Essifi, Bouajila; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2025)
This report details an on-the-job training session conducted to improve the skills of engineers and technical staff from the General Directorate of Forests (DGF) in the assessment and restoration of degraded rangelands in Central Tunisia. The training focused on evaluating rangeland conditions and implementing appropriate restoration techniques, emphasizing the use of native species and sustainable practices to enhance ecosystem resilience and productivity amid climate challenges.